The Effect of Automated versus Continuous Ambulatory Peritoneal Dialysis on Mortality Risk in China. Issue 2 (December 2018) - Li, Xuemei; Xu, Hong; Chen, Nan; Ni, Zhaohui; Chen, Menghua; Chen, Limeng; Dong, Jie; Fang, Wei; Yu, Yusheng; Yang, Xiao; Chen, Jianghua; Yu, Xueqing; et al.
Background: There is an emerging practice pattern of automated peritoneal dialysis (APD) in China. We report on outcomes compared to continuous ambulatory peritoneal dialysis (CAPD) in a Chinese cohort. Methods: Data were sourced from the Baxter Healthcare (China) Investment Co. Ltd Patient Support Program database, comprising an inception cohort commencing PD between 1 January 2005 and 13 August 2015. We used time-dependent cause-specific Cox proportional hazards and Fine-Gray competing risks (kidney transplantation, change to hemodialysis) models to estimate relative mortality risk between APD and CAPD. We adjusted or matched for age, gender, employment, insurance, primary renal disease, size of PD program, and year of dialysis inception. We used cluster robust regression to account for center effect. Results: We modeled 100, 351 subjects from 1, 178 centers over 240, 803 patient-years. Of these, 368 received APD at some time. Compared with patients on CAPD, those on APD were significantly younger, more likely to be male, employed, self-paying, and from larger programs. Overall, APD was associated with a hazard ratio (HR) for death of 0.79 (95% confidence interval [CI] 0.64 – 0.97) compared with CAPD in Cox proportional hazards models, and 0.76 (0.62 – 0.95) in Fine-Gray competing risks regression models. There was prominent effect modification by follow-up time: benefit was observed only up to 4 years follow-up, after which risk of death was similar. Conclusion: Automated peritoneal dialysis is associated with an overall lower adjusted risk of death compared with CAPD in China. Analyses are limited by the likelihood of important selection bias arising from group imbalance, and residual confounding from unavailability of important clinical covariates such as comorbidity and Kt/V.